Sea Wave Energy Simulation of Oscillating Water Column (OWC) Technology, Binongko Island, Wakatobi, Southeast Sulawesi - Mu’min Al; Gunadin Indar Chaerah; Muslimin Zaenab (E3S Web of Conferences, 2024)
Indonesia is a country that has the largest sea area of several countries spread across the world. This is an advantage for Indonesia in utilizing the energy potential of the seas and oceans. One of which is the potential of Oscillating Water Column (OWC) Technology, to utilize the energy potential of the seas and oceans not only requires sea potential but also must have location parameters with suitable seabed topography. gentle and constant sea wave height, usually influenced by wind speed. One area of Indonesia that has these parameters is Binongko Island, Wakatobi, Southeast Sulawesi, whose wave characteristics are a basic reference for exploring the enormous energy potential of the seas and oceans in that location. The author uses a simulation model with the Graphical User Interface (GUI) method in the Matlab program to determine the potential energy produced. The data used in this research uses data analysis from the Southeast Sulawesi Regional Meteorology, Climatology, and Geophysics Agency using data samples for 2021 and 2022. The data used includes sea wave height data and sea wave period data at the research location in 2021 and the 2022 time period. Through this data, it is known that Binongko Island, Wakatobi, Southeast Sulawesi 2021 will have minimum sea wave height. of 0.5125 meters and a maximum value of 1.04167 meters, for the minimum sea wave period of 2.34993 seconds and a maximum value of 3.57008 seconds, while in 2022 the minimum sea wave height will be 0.341667 meters and the maximum value will be 0.895833 meters, for a minimum sea wave period of 1.91045 and a maximum value of 3.30481 seconds. With this data, Binongko Island, Wakatobi, Southeast Sulawesi in 2021 will be able to produce a minimum of 20.8844 watts and a maximum of 75.7116 watts, while in 2022 it will be able to produce a minimum of 12.7715 watts and a maximum of 43.5652 watts.